Sami herders’ classification system of reindeer winter pastures – A contribution to adapt forest management to reindeer herding in northern Sweden - Roturier, Samuel (Rangifer, 2011)
The system for classifying vegetation types currently used in Swedish forestry has two major deficiencies when identifying reindeer winter pastures: it uses lichen cover as the sole criterion for defining them, and it ignores the possible adverse effects of snow cover. Based on ethnological field studies, this paper examines Sami reindeer herders' classification of reindeer winter pastures, and compares it to the system used by foresters at different levels of classification. At the lower level, which deals with identifying discrete entities, it is possible to find some correspondence between the representations of forest characteristics used by the Sami herders and the foresters. Reindeer herders discriminate the same factors – tree height, canopy enclosure, stem density, field-layer, bottom-layer – as forest manager, but the former use this knowledge to evaluate the effects on snow cover and ice, and thus on the accessibility of the lichen beneath. Inconsistencies appear at the second level of classification, which consists in ordering this variety of forest characteristics into a classificatory system. There is a mismatch between Sami herders and forester’s representations and classifications of pastures because Sami categories are ‘complex’, i.e. categories including many criteria that have to be combined and balanced before defining the pasture. Herders’ representation of pasture is thus holistic, rather than purely botanical. The comparison of the two classification systems demonstrates that it is impossible to define grazing quality solely in terms of lichen abundance, because of the multidimensional nature of reindeer winter pastures and consequent shifts (spatial and temporal) in its quality.